A comparative analysis study on information security threat models: a propose for threat factor profiling - Sidi, Fatimah; A. Jabar, Marzanah; Affendey, Lilly Suriani; Ishak, Iskandar; Mohd Sharef, Nurfadhlina; Zolkepli, Maslina; Tan, Ming Ming; Abd Mokthi, Muhammad Faidhi; Daud, Maslina; Zainuddin, Naqliyah; Abdul Hamid, Rafidah (Medwell Journals, 2017)
This study describes a comparative analysis study conducted on existing approaches, frameworks and relevant references used in field of information security. The purpose of this study is to identify suitable components in developing a threat factor profiling. By having a threat factor profiling, organizations will have a clear understanding of the threats that they face and enable them to implement a proactive incident management program that focuses on the threat components. This study also discusses the proposed threat factor profiling.